1998
DOI: 10.1159/000020794
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Parvovirus B19 Infection and Meconium Peritonitis

Abstract: A 33-year-old primigravida at 26 weeks gestation presented with fetal hydrops and fetal anemia following prior parvovirus B19 infection. The fetus required two intrauterine transfusions of packed red cells. At 35 weeks gestation, a cesarean section was performed for obstetric reasons. As a consequence of a prenatal bowel perforation, the neonate developed meconium peritonitis, for which she needed laparotomy. This case demonstrates that there may be an association between intrauterine parvovirus infection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 20 publications
0
21
0
3
Order By: Relevance
“…Schild et al [22] also stated the possibility of vasculitis in parvovirus B19 infection. In our series, identifiable bowel obstruction was found in only 41% (7/17) of patients, but pathological evidence of the cause of perforation was not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schild et al [22] also stated the possibility of vasculitis in parvovirus B19 infection. In our series, identifiable bowel obstruction was found in only 41% (7/17) of patients, but pathological evidence of the cause of perforation was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, congenital infection with rubella and parvovirus B19 has been reported [21,22]. However, in approximately 50% of patients, there was no detectable primary cause of bowel perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Only rare cases of fetal anomalies or malformations have been associated with B19 virus infection. These include meconium peritonitis, central nervous system and ocular abnormalities [42][43][44][45]. Furthermore, congenital red cell aplasia was observed in children treated with intrauterine blood transfusion [46] and a case of congenital B19 viremia associated with thrombocytopenic purpura and platelet antigen incompatibility was noted [47].…”
Section: Fetal Riskmentioning
confidence: 99%
“…Brown et al [13] have reported severe and persistent transfusion-dependent anaemia in 3 newborns who had suffered intra-uterine B19 infection. Schild et al [14] have reported a case of meconium peritonitis associated with fetal parvovirus B19 infection. However, other studies have shown that babies have been healthy at birth and thereafter [3,15,16].…”
Section: Discussionmentioning
confidence: 99%